The prospect of digital human communication for organizational purposes - Newman, Sean A.; Gopalkrishnan, Shalini (Frontiers in Communication, 2023)
There has been a great deal of excitement and discussion about the potential for artificial intelligence (AI) to improve business processes by providing more effective delivery options in cost-effective ways. One such way for many companies is the use of chatbots (AI paired with images of humas) as their first line of customer service communication. Using digital human technology. i.e., chabots to improve communication engagement is increasing in many companies. For example, digital human communication has advantages, such as being available any time for employees to leverage, and always having correct, vetted information to share. Even though digital human technology offers great promise for organizational communication, the potential utility will be impacted by how employees perceive the communication. For example, conversations with managers or human resources may not be as readily available as digital humans and incorrect information may at times be communicated. However, if employees have a negative bias towards digital human communication, they may not perceive it as an effective source of communication. This exploratory study was conducted to better understand how satisfied respondents are who receive communication from a digital human and their perception of the effectiveness of the communication. When subjects are exposed to a something new, they immediately make an appraisal based on their current perception which may impact their willingness to accept new technologies. The satisfaction with and perceived effectiveness of digital human communication was assessed by using mixed-methods methodology across three groups of respondents. One group heard a company announcement in person, the second group read the same announcement as an email announcement, and the last group heard the same message from an AI generated digital human. After each communication, the respondent took a survey assessing their satisfaction with the communication and perception of the communication effectiveness.